Analysis of Customer Preferences in Choosing Animal Health Care Facilities in The City of Surabaya Using Conjoint Analysis - Ramadhanty Ramadhanty; R. Mohamad Atok (Journal Research of Social Science, Economics, and Management, 2026)
The increasing number of pet owners in Surabaya City has intensified the demand for high-quality animal healthcare services; however, quantitative studies examining the service attributes that most influence customer preferences remain limited. This study aimed to identify the service attributes that most influenced customers’ decisions when selecting animal healthcare facilities in Surabaya City and to analyze the influence and relationship of demographic factors on these preferences. This study employed a conjoint analysis method involving 392 respondents. The analysis was further supported by ordinal logistic regression and Spearman and Kendall’s Tau correlation tests. The results showed that price was the most influential attribute, with a relative importance value of 52.227%, followed by service location (15.511%) and operational hours (12.757%). Other attributes, including additional facilities, veterinarian experience, and diagnostic facilities, demonstrated relatively lower levels of importance. Demographic analysis revealed that income had a consistent influence on and relationship with customer preferences, whereas age and gender did not demonstrate significant effects or relationships with customer preferences. The findings suggest that animal healthcare service providers in Surabaya City should prioritize pricing strategies and location accessibility to improve competitiveness and meet customer expectations.